PENINGKATAN HASIL BELAJAR PENDIIDIKAN PANCASILA MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE TEAMS GAMES TOURNAMENTS (TGT) BERBANTUAN WORDWALL KELAS IV SDN 27 ANAK AIR - Wahyuni, Sri; Waldi, Atri; Bungsu Ladiva, Hasmai; Ulya Akmal, Atika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning outcomes of Pancasila Education in class IV.C SDN 27 Anak Air. The purpose of this study is to determine the improvement in students' learning outcomes in Pancasila Education learning using the Cooperative Learning model of Teams Games Tournaments (TGT) type assisted by Wordwall at SDN 27 Anak Air. This research is a Classroom Action Research (CAR) which is carried out in two cycles. The research procedure consists of planning, implementation, observation, and reflection. The subjects in this study were teachers and students of class IV.C SDN 27 Anak Air with a total of 26 students. The results of the study indicate that there is an increase in students' learning outcomes in Pancasila Education learning using the Cooperative Learning model of TGT type assisted by Wordwall increasing from cycle I to cycle II which is measured based on aspects of learning planning, implementation of learning aspects of teachers and students, and aspects of students' learning outcomes measured from the value of knowledge, skills and attitudes. The results of observations on the aspect of learning planning in cycle I obtained an average of 86.1%, in cycle II increased to 97.22%. In the implementation of learning aspects of teachers and students in cycle I, the average teacher aspect in cycle I was 89.28% in cycle II to 96.42%. In the aspect of students in cycle I, the average cycle I was 78.57%, and in cycle II 92.85%. In the aspect of learning outcomes in cycle I, the average cycle I was 80.48% and in cycle II with an average of 93.89%. Based on these data, it shows an increase in learning outcomes of Pancasila Education using the TGT type Cooperative Learning model in learning in class IV.C SDN 27 Anak Air.